2010
DOI: 10.1007/s11262-010-0453-z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of two Chinese strains of porcine reproductive and respiratory syndrome viruses with different virulence

Abstract: Two strains of porcine reproductive and respiratory syndrome virus (PRRSV) were isolated, designated GDQJ and GDBY1. Experimental inoculation showed that GDBY1, caused 100% morbidity and 67% mortality, while GDQJ, caused 100% morbidity but no death. Full-length genomes were sequenced. Homologic and phylogenetic analyses indicated that these two strains were closely related to Chinese highly pathogenic PRRSV strains. Surprisingly, identical 30 amino acids (aa) deletion in the NSP2-coding region, a presumed high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Publications that linked genotype and phenotype were a minor component of GenBank accessions (Brockmeier et al, 2012;Darwich et al, 2011;Díaz et al, 2006;Gauger et al, 2012;Kim et al, 2007;Lee et al, 2004;Li et al, 2010;Martínez-Lobo et al, 2011a, b;Yu et al, 2013). Moreover, as the phenotypes examined can vary among genotype/ phenotype studies, comparisons between isolates can still be cumbersome and ambiguous.…”
Section: Beyond Prrsv Diversitymentioning
confidence: 99%
“…Publications that linked genotype and phenotype were a minor component of GenBank accessions (Brockmeier et al, 2012;Darwich et al, 2011;Díaz et al, 2006;Gauger et al, 2012;Kim et al, 2007;Lee et al, 2004;Li et al, 2010;Martínez-Lobo et al, 2011a, b;Yu et al, 2013). Moreover, as the phenotypes examined can vary among genotype/ phenotype studies, comparisons between isolates can still be cumbersome and ambiguous.…”
Section: Beyond Prrsv Diversitymentioning
confidence: 99%
“…Different strains of PRRSV have been shown to present the differential pathogenicity for pigs (Brockmeier et al, 2012;Li et al, 2010b;Zhou et al, 2009a). Moreover, the continuous evolution of PRRSV results in the generation of novel or variant strains that cause severe clinical syndromes (Halbur and Bush, 1997;Han et al, 2006;Karniychuk et al, 2010;Tian et al, 2007;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the isolates revealed this virus was derived from endemic Type 2 PRRSV, and a common set of mutations (discontinuous deletions in nsp2) was identified that has been used as a molecular marker for HP-PRRSV isolates [4][5][6][7]. However, it is not definitive if the common mutations are related to the phenotype [8,9]. Following the initial Chinese reports, PRRSV isolates with similar nsp2 deletions were recovered from high mortality epidemics in contiguous countries indicating probable regional spread of the virus in Southeast Asia [10,11].…”
Section: Introductionmentioning
confidence: 99%